TRANSAKSI DAN POS NERACA PEMBAYARAN INTERNASIONAL - Rohmah, Nurlaili; Hasbi, M. Zidny Nafi' (IJMA (Indonesian Journal of Management and Accounting), 2021)
Indonesia as a country that adheres to an open economic system, the dominant economic activity in increasing economic growth is domestic private consumption, as well as investment and international trade activities that have a positive impact on economic growth, especially for the Indonesian economy. Where these economic activities are related to payment system activities. The positive impact of technological developments and advances is the strongest support for creating the latest innovations in the payment system. Where it is explained that credit is a transaction that gives rise to the right to receive payments from residents of other countries, while debit is a transaction that creates an obligation to pay to residents of other countries. The balance of payments is a systematic record or report related to all economic transactions between residents of one country and other countries within a certain period. The balance of payments will provide an overview of the government regarding the country's international position and be able to assist in the formulation of monetary, fiscal and trade policies